Training a Chorus in Ancient Greece (Gilgameš, 2019)
In this paper, I shall analyse the information we can extract fromancient Greek texts about the training of those citizens chosen tobecome members of a chorus during the Athenian festivals, as wellas the importance to become such. I shall offer a revision of the roleof the chorodidaskalos, the person in charge of their instruction,considered, in a certain way, a maestro di canto in the ancient world,in order to determine if we can delimit the professional groundswith which they used to work, from a technical point of view,especially when, in many cases, they had to deal with members notprofessionally educated for their chorus lines. This panorama willshow the importance that the practice of singing within a chorus,principally on an Athenian theatre, implied for those citizens whopartook their experience at each festival, and how things weredealt with from the Classical period until we find the phonaskos, aprofessional trainer of voice that appears in the Greek world fromthe Roman period onwards.